P253 Could application of simple diagnostic algorithm aid onward referral for optimisation of pre-existing conditions in patients being considered for major surgery?. (15th November 2016) - Hornsby, J; Higgins, P; Baker, A; Black, E; Anderson, D
Abstract : Introduction: Cardiopulmonary exercise testing (CPET) is used to identify physiological limitation to exercise and aid diagnosis of cardiorespiratory, psychological and muscle disorders. 1 It is also frequently used to stratify operative risk thereby aiding decision making in patients considered for major surgical procedures. 2 The evidence for risk stratification is based on the oxygen consumption at anaerobic threshold (VO2 AT) along with metabolic equivalence. 2 Attention is therefore generally paid to the numerical value of these measures rather than full interpretation of the data. Further interpretation may allow further diagnosis and optimisation of pre-existing conditions. Methods: We retrospectively applied a simple diagnostic algorithm (Figure 1 ) to CPETs undertaken by patients considered for major surgery in the Victoria Infirmary, Glasgow between 2014–2016. Results: The records of 39 patients who had a pre-operative CPET testing were analysed: 22 male, 17 female, age range 43–88, median 73.A total of 26 patients were classified as high risk, 23 achieved an AT <11 mls/kg/min and 3 with a metabolic equivalent <4.0mls02 /kg/min. Both parameters were low in 13 patients. Ten patients had their procedures cancelled due to this. Eleven high risk patients had a normal VO2 max. Upon applying the diagnostic algorithm; 15 patients were deconditioned, 6 had cardiovascular limitation, 3 had respiratory limitation and 15 were normal. In the 'high risk' population: 2 patients had respiratory limitation with pre-existing respiratory conditions and were cancelled. Six patients had cardiovascular limitation with 3 patients having pre-existing cardiac diagnosis, 3 were cancelled. Seven of the patients were 'deconditioned'; 5 were cancelled as a result. Conclusion: This algorithm suggests that 8 patients were considered high risk as a result of cardiorespiratory disease and a further 7 as a result of deconditioning. Appropriate speciality review and intervention or an exercise prescription pre-operatively might allow patients to improve their operative risk and therefore to proceed to major surgery. References: Cooper C, Storer T. Exercise testing and interpretation. A practical approach . Edinburgh: Cambridge University Press, 2001. Moran J, et al . Role of cardiopulmonary exercise testing as a risk-assessment method in patients undergoing intra-abdominal surgery: a systematic review. BJA 2016;116 (2):177–191.